Service Operations Practice and Performance of Local Authorities in Malaysia - Mohd Nazri Zakaria; Abdullah Al- Mamun; Noorshella Che Nawi; Razli Che Razak (2015)
Operation management commonly deals with design, management, planning, coordination, and control of resources needed for the production of goods and services (Reid & Sanders, 2007).Operation practices have a significant influence on an organization's ability to compete in the market (Narasimhan et al., 2005; Ward & Zhou, 2006). However, most studies only focused on specific operation practices such as quality management practices (Khairul, 2002), just in time practices (Flynn et al., 1995) and human resource management practices (Chen & Huang, 2009).